A natural hybrid of Anoectochilus (Orchidaceae) from Xizang, China - Li, Chen Xing; Liu, Yue; Shi, Bei Bo; Sun, Mei; Huang, Jing; Liu, Zhen; Tian, Huai Zhen (Phytotaxa, 2024)
Anoectochilus × buqunhuensis, a natural hybrid new to science is described from Xizang Autonomous Region, China. A detailed morphological description with dissection photographs, line drawings and molecular data of plastid DNA (matK, rbcL, trnL-F) and nuclear DNA (ITS) are provided to identify the hybrid and the parental species (A. griffithii and A. medogensis).